THE EFFECT OF COGNITIVE DISSONANCE ON ACCOUNTING FRAUD BEHAVIOR WITH ACCOUNTING MORAL AS A MODERATING VARIABLE IN ACCOUNTING STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS, PATTIMURA UNIVERSITY, AMBON - Rita J D Atarwaman; Adelyn Abarua; Frangky Richard Limaheluw; Wa Pujji (PT. Jurnal Center Indonesia Publisher, 2026)
Accounting fraud remains a critical ethical issue that threatens the credibility of the accounting profession. This study aims to examine the effect of cognitive dissonance on accounting fraud behavior and to analyze the moderating role of accounting morality in weakening this relationship. The research employs a quantitative approach using Moderated Regression Analysis (MRA). Data were collected from 120 accounting students of the Faculty of Economics and Business, Universitas Pattimura Ambon, selected through purposive sampling. The results indicate that cognitive dissonance has a positive and significant effect on accounting fraud behavior. Furthermore, accounting morality is proven to significantly moderate the relationship by weakening the influence of cognitive dissonance on fraudulent behavior. These findings support Cognitive Dissonance Theory and Moral Development Theory, emphasizing the importance of strengthening ethical education to reduce fraudulent tendencies among future accounting professionals.